Mongolia - Towards a High Performing Civil Service : Reform Progress and Challenges - World Bank (World Bank, Ulaanbaatar, 2021)
This report reviews Mongolia’s civil service in the ten years since the World Bank’s (WB) 2009 civil service assessment. An important milestone was the passing of a new Civil Service Law (CSL) in late 2017, by the State Great Hural, which became effective January 1, 2019. This report reviews recent developments in the light of the new law, paying particular attention to three areas critical to successful implementation. The report is optimistic that Mongolia, with stronger foundations in place, is now better placed to move forward improving the efficiency and effectiveness of the civil service. However, this will require determined leadership, with some important, challenging strategic and technical decisions to make on the way forward. The report ends with a chapter of conclusions and recommendations, with suggestions on sequencing and how to monitor and evaluate the new arrangements.